A three-phase interpenetrating continua approach for wave and porous structure interaction. Issue 3 (14th May 2020) - Yang, Liang; Buchan, Andrew; Pavlidis, Dimitrios; Jones, Alan; Smith, Paul; Sakai, Mikio; Pain, Christopher
Abstract : Purpose: This paper aims to propose a three-phase interpenetrating continua model for the numerical simulation of water waves and porous structure interaction. Design/methodology/approach: In contrast with one-fluid formulation or multi-component methods, each phase has its own characteristics, density, velocity, etc., and each point is occupied by all phases. First, the porous structure is modelled as a phase of continua with a penalty force adding on the momentum equation, so the conservation of mass is guaranteed without source terms. Second, the adaptive unstructured mesh modelling with P1DG-P1 elements is used here to decrease the total number of degree of freedom maintaining the same order of accuracy. Findings: Several benchmark problems are used to validate the model, which includes the Darcy flow, classical collapse of water column and water column with a porous structure. The interpenetrating continua model is a suitable approach for water wave and porous structure interaction problem. Originality/value: The interpenetrating continua model is first applied for the water wave and porous structure interaction problem. First, the structure is modelled as phase of non-viscous fluid with penalty force, so the break of the porous structure, porosity changes can be easily embedded for further complex studies. Second, the mass conservation of fluids is automatically satisfied without special treatment. Finally, adaptive anisotropic mesh in space is employed to reduce the computational cost.